2024
DOI: 10.1001/jama.2024.1059
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Risk After COVID-19 Bivalent Vaccination Among US Older Adults

Yun Lu,
Kathryn Matuska,
Gita Nadimpalli
et al.

Abstract: ImportanceIn January 2023, the US Centers for Disease Control and Prevention and the US Food and Drug Administration noted a safety concern for ischemic stroke among adults aged 65 years or older who received the Pfizer-BioNTech BNT162b2; WT/OMI BA.4/BA.5 COVID-19 bivalent vaccine.ObjectiveTo evaluate stroke risk after administration of (1) either brand of the COVID-19 bivalent vaccine, (2) either brand of the COVID-19 bivalent plus a high-dose or adjuvanted influenza vaccine on the same day (concomitant admin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this SCCS study, the risk of nonhemorrhagic stroke (NHS), transient ischemic attack (TIA), NHS and/or TIA (NHS/TIA), and hemorrhagic stroke (HS) following exposure to a high-dose or adjuvanted influenza vaccine was evaluated among persons 65 years or older (primary analysis) and by age subgroup (65-74, 75-84, and ≥85 years). 1 , 2 , 3 Fixed risk windows (1-21 and 22-42 days) were compared with a control window (43-90 days). For each influenza season, the study period began on the first Sunday of August and ended 1 day before the start of the subsequent season.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this SCCS study, the risk of nonhemorrhagic stroke (NHS), transient ischemic attack (TIA), NHS and/or TIA (NHS/TIA), and hemorrhagic stroke (HS) following exposure to a high-dose or adjuvanted influenza vaccine was evaluated among persons 65 years or older (primary analysis) and by age subgroup (65-74, 75-84, and ≥85 years). 1 , 2 , 3 Fixed risk windows (1-21 and 22-42 days) were compared with a control window (43-90 days). For each influenza season, the study period began on the first Sunday of August and ended 1 day before the start of the subsequent season.…”
Section: Methodsmentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) investigated stroke risk following COVID-19 bivalent and influenza vaccines among Medicare beneficiaries 65 years or older in 2022 and 2023 . The self-controlled case series (SCCS) study found no consistent evidence of stroke risk in the days following COVID-19 bivalent vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Another SCCS study conducted in Israel also did not find an increased risk of ischemic stroke following monovalent or bivalent mRNA COVID-19 vaccine boosters in at-risk populations [ 15 ]. A study of Medicare beneficiaries aged 65 years or older showed no significantly elevated risk for stroke immediately after receiving either COVID-19 bivalent vaccine [ 16 ]. However, among beneficiaries who had a stroke after getting either COVID-19 bivalent vaccine along with a high-dose or adjuvanted influenza vaccine, there was a significant association between vaccination and nonhemorrhagic stroke within 22 to 42 days for the Pfizer-BioNTech COVID-19 bivalent vaccine.…”
Section: Introductionmentioning
confidence: 99%